A Periodic Solution of the Generalized Forced Liénard Equation - Zahra Goodarzi; Abdolrahman Razani (Abstract and Applied Analysis)
We consider the generalized forced Liénard equation as follows: (ϕp(x′))′+(f(x)+k(x)x′)x′+g(x)=p(t)+s. By applying Schauder's fixed point theorem, the existence of at least one periodic solution of this equation is proved.